Antitumor activity of ruthenium(II) complexes on HCT 116 cell line in vitro - Zelen, Ivanka; Zarić, Milan; Čanović, Petar P; Igrutinović, Danica; Rilak Simović, Ana (Education and Research in Health Sciences, 2022)
In the field of non-platinum complexes, ruthenium complexes have shown very strong antitumor activity on various types of cisplatin-resistant tumors. In addition, Ru(II) and Ru(III) complexes have shown a high degree of selectivity towards cancer cells as well as antimetastatic effects. Importantly, ruthenium compounds can bind to the DNA molecule of a tumor cell and thus reduce the viability of cancer cells. Moreover, ruthenium complexes can bind to human serum albumin and transferrin, which makes their transfer to tumor cells more efficient than platinum compounds. Consequently, the research aim was to investigate the antitumor effect of two synthesized Ru(II) complexes [Ru(Cl-Ph-tpy)(phen)Cl]Cl (K1) and [Ru(Cl-Ph-tpy)(o-bqdi)Cl]Cl (K2) on the HCT 116 cell line, and to define the mechanism of cell death that these compounds induce in HCT 116 cancer cells. Results of our research clearly showed that the two investigated ruthenium complexes K1 and K2 showed very strong antitumor activity against the HCT 116 tumor cell line. Additionally, ruthenium complex K1 showed higher antitumor activity than ruthenium K2 complex and cisplatin after 72 hours of treatment. Our findings demonstrated that both K1 and K2 ruthenium compounds exhibited strong antitumor activity against HCT 116 cell line by induction of early apoptosis.